Mengungkap Makna di Balik Tarian Tradisional Pepe-pepe ri Makkah Pada Masyarakat Makassar - Jamilah; Andi Padalia; Nurachmy Sahnir (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This article aims to uncover the cultural significance behind the Pepe-pepe ri Makkah dance, one of the traditional dances originating from Makassar, South Sulawesi, Indonesia. The research method employed is qualitative research with a descriptive-analytical approach. Data collection was conducted through direct observation, interviews with performers or dancers, and literature review. The research findings indicate that the Pepe-pepe ri Makkah dance embodies profound religious and spiritual meanings, symbolizing gratitude and reverence to God, expressed through captivating movements involving torches or fire props. The collaborative interaction among dancers carries social and communal significance, as the Makassar community uses this dance as a means to strengthen relationships among its members. This article contributes significantly to the cultural richness of Indonesia, particularly in preserving and developing Makassar's traditional dance heritage.